2015
DOI: 10.1002/btpr.2149
|View full text |Cite
|
Sign up to set email alerts
|

Production of lignosulfonate in NSSC‐based biorefinery

Abstract: The spent liquor (SL) of a neutral sulfite semichemical (NSSC) pulping process contains a considerable amount of lignocelluloses and is treated in wastewater systems. The lignocelluloses, however, can be used for producing value-added products if they are isolated from the SL. In this article, solvent treatment (mixing acetone, ethanol, or isopropyl with SL) was used as a method for isolating lignosulfonate from SL. The maximum lignosulfonate removal was obtained via mixing isopropyl alcohol with SL at the wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a study referenced by Aro and Fatehi (2017), the increase in molecular weight to 14 000 g mol -1 improved heat stability, dispersibility of dye, and dye adsorption. Similarly, Tarasov et al (2015) also concluded in their research that lignin with a large molecular weight may be used as a dispersant.…”
Section: Lignin Categories and Use For Dye Dispersantsmentioning
confidence: 95%
“…In a study referenced by Aro and Fatehi (2017), the increase in molecular weight to 14 000 g mol -1 improved heat stability, dispersibility of dye, and dye adsorption. Similarly, Tarasov et al (2015) also concluded in their research that lignin with a large molecular weight may be used as a dispersant.…”
Section: Lignin Categories and Use For Dye Dispersantsmentioning
confidence: 95%
“…Due to its low cost, hydrophobic nature, and its suitability for attachment of hydrophilic groups, there has been interest in the development of surfactants based on lignin (Uraki et al 2012;Sipponen et al 2019). In particular, sodium lignosulfonate is a low-cost surfactant byproduct of the sulfite pulping of wood (Rueda et al 2015;Tarasov et al 2015). Sodium lignosulfonate has been shown to be effective in such applications as enzymatic saccharification of lignocellulose (Wang et al 2013;Zhou et al 2013), and the preparation of polyurethane foams (Hatakeyama et al 2003).…”
Section: Bio-based Detergents (Fatty Acid Components)mentioning
confidence: 99%
“…The gradual exhaustion of petroleum resources and the environmental problems resulting from the excessive use of fossil resources pose a threat to the sustainable development of human society. Thus, more attention has focused on the utilization of renewable energy materials that could partly or even completely replace fossil products (Tarasov et al 2015;Li et al 2016a;Patel and Kumar 2016;Qin et al 2016;Rudie et al 2016). Today, the exploration of high-value chemicals produced from biomass resources is becoming one of the most important approaches to determining applications of renewable materials.…”
Section: Introductionmentioning
confidence: 99%